2006
DOI: 10.1111/j.1439-0418.2006.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on biology and population growth parameters ofAphis gossypiiGlover (Hom., Aphididae) on greenhouse cucumber

Abstract: Temperature-dependent development, survivorship and reproduction of the cotton aphid, Aphis gossypii on Cucumis sativus L. were evaluated at six constant temperatures (10, 15, 20, 25, 30 and 35°C). Developmental periods of immature stages varied from 20.70 days at 10°C to 3.81 days at 30°C. The population failed to survive at 35°C. As temperature increased, the intrinsic rate of increase (r m ) followed a typical asymmetrical dome-shape pattern, with maximum value of 0.419/day at 25°C. Survival of immature sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 38 publications
6
54
0
3
Order By: Relevance
“…The shorter adult longevity under field conditions might be due to the high temperature and the higher humidity. Zamani et al (2006) reported that developmental time of A. gossypii reared on Cucumis sativus L. under laboratory conditions, was inversely related to temperature. Satar et al (2005) reported that developmental periods of immature stages of A. gossypii under laboratory conditions, ranged from 10.8 days at 15°C to 4.1 days at 30°C and 32.5°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shorter adult longevity under field conditions might be due to the high temperature and the higher humidity. Zamani et al (2006) reported that developmental time of A. gossypii reared on Cucumis sativus L. under laboratory conditions, was inversely related to temperature. Satar et al (2005) reported that developmental periods of immature stages of A. gossypii under laboratory conditions, ranged from 10.8 days at 15°C to 4.1 days at 30°C and 32.5°C.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the effect of temperature on the biology and population growth parameters, development, and fecundity of A. gossypii reared on cucumber and Cucurbita pepo L. under laboratory conditions (Wyatt and Brown 1977;Aldyhim and Khalil 1993;Kocourek et al 1994;Satar et al 2005;Zamani et al 2006). However, nothing has been done under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bing et al (1991) reported that corn leaf aphids attack maize in coleoptiles and at two/four leaf stages, and decrease its growth and height with ensuing pollen fall and hindrance of plant silking. Several aphid species, such as Aphis gossypii (Razmjou et al, 2006;Zamani et al, 2006), R. padi (Asin and Pons, 2001), and Aphis fabae Scopoli (Kuroli and Lantos, 2008) display comparable behavior on their hosts. Therefore, decreasing aphid density through the use of hybrids with low supporting aphid populations would be very important both early and late in the corn-growing season.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Satar et al (2005), the average reproductive rate of A. gossypii was 82.1 nymphs/female at 25°C but only 2.3 nymphs/female at 32.5°C; in addition, the highest per capita growth rate (r m = 0.526) occurred at 25°C and the lowest at 32.5°C (r m = 0.132). However, a constant temperature of 35°C was found to be lethal to the immature stages of A. gossypii (Kersting et al 1999;Zamani et al 2006). The high temperatures that prevailed during our study may thus have hurt aphid populations and delayed the development of high aphid populations at an early stage of plant growth (Kersting et al 1999;Xia et al 1999).…”
Section: Discussionmentioning
confidence: 74%
“…A basic life table constructed for A. gossypii on cucumber and cotton showed that the optimal temperature for population growth was 25°C, while temperatures above 30°C prolonged development, increased mortality of immature stages, shortened adult longevity and reduced fecundity (Kersting et al 1999;Satar et al 2005;Zamani et al 2006). In a study conducted by Satar et al (2005), the average reproductive rate of A. gossypii was 82.1 nymphs/female at 25°C but only 2.3 nymphs/female at 32.5°C; in addition, the highest per capita growth rate (r m = 0.526) occurred at 25°C and the lowest at 32.5°C (r m = 0.132).…”
Section: Discussionmentioning
confidence: 99%